ANALISIS TINGKAT KESEHATAN BANK DENGAN MENGGUNAKAN METODE CAMEL: STUDI PADA PT BANK MANDIRI DAN PT BANK CENTRAL ASIA TAHUN 2022-2024 - Al Amin, Muhammad Ridho; Darmayanti, Elmira Febri; Cahyani, Vanya (Universitas Muhammadiyah Metro, 2025)
The bank is one of the means for the community as a place to save money. The task of the bank is to raise funds and channel customer funds and provide services. This study aims to analyze the level of bank health of the two banks, namely PT Bank Mandiri Tbk and PT Bank Central Asia Tbk using the CAMEL method which includes aspects of Capital, Assets, Management, Earning, and Liquidity. The analysis method used is descriptive qualitative method. The research instrument in this study is in the form of financial statement documents from the two banks. PT Bank Mandiri Tbk and PT Bank Central Asia Tbk in 2022-2024. The results showed that based on calculations using the CAMEL method, the two banks, PT Bank Mandiri Tbk and PT Bank Central Asia Tbk, there were advantages possessed by each bank from the five aspects of CAMEL. Both banks, PT Bank Mandiri Tbk and PT Bank Central Asia Tbk show the health level of the bank with “Healthy” indicators.